Neurodevelopmental Outcome of Children With Spina Bifida Aperta Repaired Prenatally vs Postnatally: Systematic Review and Meta-analysis. Issue 8 (August 2019) - Inversetti, A.; Van der Veeken, L.; Thompson, D.; Jansen, K.; Van Calenbergh, F.; Joyeux, L.; Bosteels, J.; Deprest, J.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2019;53:293–301) Spina bifida aperta is characterized by a congenital defect in the vertebral arches, with protrusion of the meninges and, in the case of myelomeningocele, protrusion of the spinal cord as well. In the majority of cases, spina bifida is not lethal in the neonatal period, although it is associated with higher mortality than in the normal population (44, 000 deaths in 150, 000 affected newborns per year worldwide).